PENERAPAN LEMBAR KERJA PESERTA DIDIK BERBASIS DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF KELAS X IPA.1 SMA NEGERI 1 TEMPULING - Mailisa Susanti; Sri Wulandari; L.N. Firdaus L.N. Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract :This research aimed to improve students creative thinking skills in class X IPA.1 SMA Negeri 1 Tempuling by implementation worksheets based on discovery learning. The methods of this research was classroom action research. It had been done in two cylce. There were planning step, acting step, observation step and reflection step for each cycle. The research was carried in SMA Negeri 1 Tempuling on September-October 2018. Parameters measure were creative thinking skill as seen from the answers of students on worksheet and assessed using the creative thinking skill assessment sheet. The collected data was analysed descriptively. The results of this research showed that creative thinking skill on first cycle was 59.80 (creative) and increased on second cycle up to 85.87 (very creative). It can be conclude that implementation worksheets based on discovery learning can improve creative thingking skill of students class X IPA.1 SMA Negeri 1 Tempuling. Key Words : Creative Thinking Skills, Discovery Learning, Worksheets